Effect of moisture and bale type on alfalfa hay quality and digestibility - Laytimi, A.; Grimes, C.; Bolsen, K. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Third cutting alfalfa was baled in large rectangular bales (1,400 to 1,800 lb) and in small conventional bales (70 to 90 lb) at three moisture levels: low 00%), medium (16%), and high (22%). During 120 days of storage under a roof, the high moisture, large bales heated the most, reaching 1280 F by 2 days post-baling in a first peak and 133 ̊F in a second peak by the 11th day. Moderate heating occurred in the high moisture, small bales (l08° F) and medium moisture, large bales (103 ̊F). Only the high moisture bales, either small or large, had significant dry matter loss during storage. Also, heating decreased water soluble carbohydrates and increased the concentration of cell wall contents by the end of storage. A three-period collection and digestion trial with lambs showed higher voluntary intakes of small bale hays than of large bale hays and higher intakes of high moisture hays than of low moisture hays. Also, the dry matter and crude protein digestibilities were lowest for the high moisture, large bales. Storing alfalfa hay in large bales at 22% moisture resulted in extensive heating, which increased storage loss and decreased nutrient content and digestibility.
Keywords: Beef; Moisture; Quality; Digestibility